2012
DOI: 10.1016/j.biortech.2011.10.061
|View full text |Cite
|
Sign up to set email alerts
|

The effect of particle size and thermal pre-treatment on the methane yield of four agricultural by-products

Abstract: One way to optimize methane production in anaerobic digestion plants is to substitute ligno-cellulosic by-products for crops traditionally used as energy sources. However, using these by-products requires introduction of a pre-treatment system to minimize energy input and maximize energy output for an improved net energy equation. In this study, four agricultural byproducts (wheat, barley, rice straw and maize stalks) underwent various mechanical and thermal treatments prior to anaerobic digestion including pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
80
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(91 citation statements)
references
References 21 publications
9
80
1
1
Order By: Relevance
“…In their pilot-scale experiment, Schell and Harwood 66 showed that lignocellulose particle size of 1 to 2 mm is effective for hydrolysis. Menardo et al 67 conducted various mechanical and thermal treatments prior to AD of four agricultural byproducts. An net electrical energy balance was also completed to analyze the feasibility of the pretreatments according to energy input and output.…”
Section: Mechanical Pretreatmentmentioning
confidence: 99%
“…In their pilot-scale experiment, Schell and Harwood 66 showed that lignocellulose particle size of 1 to 2 mm is effective for hydrolysis. Menardo et al 67 conducted various mechanical and thermal treatments prior to AD of four agricultural byproducts. An net electrical energy balance was also completed to analyze the feasibility of the pretreatments according to energy input and output.…”
Section: Mechanical Pretreatmentmentioning
confidence: 99%
“…Agro-industrial byproducts and residues are often used as the broadcast source of the substrate for anaerobic biotransformation to biogas, which suggests that byproduct substrates could be alternatives to energy crops in anaerobic digestion plants (Menardo et al 2012). Although biomass energy is more costly than fossil fuel-derived energy, trends to limit carbon dioxide and other emissions through emission regulations, carbon taxes, and subsidies of biomass energy would make it cost competitive (Chynoweth et al 2001;Charters 2001), even when low-cost treatment, due to high energy recovery and environmentally friendly are taken into consideration (Ferreira et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…hectare in Germany [35]. With increasing competition for land and food, together with natural resources such as water and nutrients, the AD sector has typically focused on deriving energy from wastes and residues [6]. However, a number of second-generation energy crops are emerging that have shown good potential as feedstocks for bio-energy and particularly AD.…”
Section: Purpose Grown Energy Cropsmentioning
confidence: 99%
“…Treatments at temperatures of 130, 150 and 170 • C all led to sludge reduction, with higher temperatures leading to a reduction in volatile solids of up to 80% compared to controls. Menardo [6] noted increased methane yields of up to 40% when applying 90 • C thermal pre-treatment to wheat and barley straw; however, negligible improvements were noted for maize straw and rice stalks having received the same …”
Section: Thermal Pre-treatmentmentioning
confidence: 99%